Analisis Kerentanan Banjir Menggunakan Metode Normalised Morphometric Flood Index (NMFI) Studi Khusus: SubDAS Air Manna, Bengkulu Selatan - Islam, Muhammad Izzul; Setiawan, Budhi (OPHIOLITE: Jurnal Geologi Terapan, 2024)
Air Manna River is the main river that accommodates water flow from small rivers in the Air Manna sub-watershed. This river has a reasonably large water discharge. One way to determine a watershed's flood disaster potential is by using the morphometric aspect approach to the watershed. After analysing the morphometric parameters, it was found that some areas in the Air Manna sub-watershed have high flood potential. These areas are areas with high drainage density values, high main channel slope in the river flow, low length of overland flow values, high ruggedness number, and low bifurcation ratio values. Furthermore, the results of the morphometric parameter analysis of the research area will be normalized using the Normalized Morphometric Flood Index (NMFI) method. NMFI simplifies the values of the morphometric parameter analysis results into the range 0 - 1, which aims to reduce the subjectivity of the analysis results so that it will increase the accuracy of the analysis data. Based on the results of processing with the NMFI method, three levels of flood hazard were obtained, i.e. low, medium, and high, which are depicted by green, yellow, and red colours on the map. Areas with low hazard levels amounted to 5.98% or 2009.75 km2, medium hazard levels amounted to 80.09% or 26916.64 km2, and areas with high hazard levels amounted to 13.92% or 4678.23 km2.